PERBANDINGAN PELELANGAN PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK BERDASARKAN ATURAN PERPRES RI NOMOR 70 TAHUN 2012 DAN PERPRES RI NOMOR 4 TAHUN 2015 DI KABUPATEN KUTAI KARTANEGARA TENGGARONG - ACHMAD, MIRZA (KURVA S JURNAL MAHASISWA, 2017)
The auction is the procurement of goods and services that are conducted openly with theannouncement widely through printed media, electronic media and official announcement boardso that the broad community / business world who are interested and have the qualification canfollow it. The auctions implemented by the government, especially in the Kutai Kartanegaradistrict of East Kalimantan are now carried out electronically.With the aim of providing input and solutions in improving the understanding of electronicprocurement system / goods. With the identification to know and understand the comparison ofauction system implemented based on Presidential Regulation 70 of 2012 and PresidentialRegulation 4 of 2015 in Kutai Kartanegara Regency.The method used in data collection is by way of questionnaires and interviews to the users ofservices and service providers. While the data analysis method using SPSS software version 16.00.From the analysis result, it can be concluded with the procurement system of goods / servicesbased on Perpres 70 of 2012 and Perpres 4 year 2015 in Kutai Kartanegara Regency resulted thecomparison of positive and easy-to-understand system for both service users and serviceproviders.